TUJUAN KHUSUS HUKUM ISLAM DALAM KEWAJIBAN NAFKAH SUAMI: PENDEKATAN NORMATIF TERHADAP PERLINDUNGAN HAK EKONOMI PEREMPUAN - Muhammad Jamaludin Faiz; Nuril Khasyi’in (PT. Hasba Edukasi Mandiri, 2026)
This study analyzes the concept of nafaqah (maintenance) in Islamic family law as a fundamental instrument that reflects the maqasid al-shari‘ah orientation in preserving the continuity and stability of the family institution. Through a normative legal approach, this research examines the structure of maintenance obligations by exploring primary sources of the Sharia, including the Qur’an, hadith, classical fiqh, and modern regulations, and integrates them with conceptual findings from contemporary academic literature. The analysis shows that maintenance is positioned not merely as an individual obligation of the husband, but as a Sharia-based mechanism that carries a protective function for three essential objectives: the protection of life (hifz al-nafs), the protection of lineage (hifz al-nasl), and the protection of property (hifz al-mal). This study affirms that the obligation of maintenance is a direct manifestation of Islamic legal construction oriented toward public welfare (maslahah), and remains relevant as a legitimizing basis for positive legal norms that govern and enforce the distribution of economic responsibilities within the household. Thus, maintenance possesses strategic value as both a juridical and moral instrument in realizing a stable, just family structure that aligns holistically with the objectives of the Sharia.